Hyper Crosslinked Polystyrene Based Materials for Carbon Dioxide Capture Applications - Adam, Ethan Nicholas (Curtin University, 2022)
This thesis investigates various hyper crosslinked polystyrene materials and their combinations with amines and amine blends, as well as the synthesis of novel materials such as the betaine-taurine ionic liquid and a RAFT based polystyrene-VDMA copolymer nanogel for the purposes of CO2 capture applications.